Non‐invasive recanalization of deep venous thrombosis by high frequency ultrasound in a swine model with follow‐up. (6th September 2020) - Goudot, Guillaume; Khider, Lina; Del Giudice, Costantino; Mirault, Tristan; Galloula, Alexandre; Bruneval, Patrick; Julia, Pierre; Sapoval, Marc; Houdouin, Alexandre; Tanter, Mickaël; Suarez, Daniel; Rémond, Mathieu; et al.
Abstract: Aims: Pulsed cavitational ultrasound therapy (thombotripsy) allows the accurate fractionation of a distant thrombus. We aimed to evaluate the efficacy and safety of non‐invasive thrombotripsy using a robotic assisted and high frequency ultrasound approach to recanalize proximal deep venous thrombosis (DVT) in a swine model. Methods: Occlusive thrombosis was obtained with a dual jugular and femoral endoveinous approach. The therapeutic device was composed of a 2.25 MHz focused transducer centered by a linear ultrasound probe, and a robotic arm. The feasibility, security, and efficacy (venous channel patency) assessment after thrombotripsy was performed on 13 pigs with acute occluded DVT. To assess the mid‐term efficacy of this technique, 8 pigs were followed up for 14 days after thrombotripsy and compared with 8 control pigs. The primary efficacy endpoint was the venous patency. Safety was assessed by the search for local vessel wall injury and pulmonary embolism. Results: We succeeded in treating all pigs except two with no accessible femoral vein. After median treatment duration of 23 minutes of cavitation, all treated DVT were fully recanalized acutely. At 14 days, in the treated group, six of the eight pigs had a persistent patent vein and two pigs had a venous reocclusion. In the control group all pigs had a persistent venous occlusion. At sacrifice, no local vein nor arterial wall damage were observed as well as no evidence of pulmonary embolism in all pigs. Conclusion: High frequency thrombotripsy seems to be effective and safe for non‐invasive venous recanalization of DVT.